Kak Taubeka Dva: on the Image of Amiable Love - Plejić-Poje, Lahorka; Rudan, Evelina (Poznańskie Studia Slawistyczne, 2021)
This paper is aimed at scrutinizing emblematic and iconic functions of doves in love poetry. Despite the fact that love is a complex emotion both in literary and psychological sense, the main analytical emphasis will be put on the literary codification of a simple (amiable) type of love – incarnated in the symbol of dove – within various cultural layers. In addition to this, it will be argued that a dove or a pair of pigeons as literary topoi are very common in popular and oral literature as opposed to the literature with the certain authorship. The aforesaid literary image can frequently be found in Kajkavian manuscripts of love poetry which originated from the 18th and 19th centuries. Moreover, it will be demonstrated that this image is still present in a popular music of the 20th and 21st century.